PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK DAN AUDIT FEE TERHADAP AUDIT DELAY (STUDI EMPIRIS PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BEI) - El Wanda, Rachel Jelita; Mialasmaya, Siti (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2025)
This research is conducted to determine the effect of Public Accountant Firm Reputation and Audit Fee on Audit Delay at Public Accountant Firms (An Empirical Study of Financial Sector Companies Listed on the Indonesia Stock Exchange). The data used in this study consists of secondary data obtained from www.idx.co.id. The population in this study includes 105 financial sector companies listed on the Indonesia Stock Exchange up to the 2024 period. Using the Slovin method and objective sampling, 51 companies that met the criteria were selected as samples. The data analysis method utilized is PLS (Partial Least Squares), with data processed using SmartPLS software. The results of this study indicate that the reputation of Public Accounting Firms has a negative and significant effect on Audit Delay, and Audit Fee also has a negative and significant effect on Audit Delay. In summation, Audit Delay will decrease with the increase in the Reputation of Public Accounting Firms and Audit Fee.